2018
DOI: 10.15655/mw/2018/v9i1/49275
|View full text |Cite
|
Sign up to set email alerts
|

Journalism Education in the GCC Region:University Students’ and Professionalism Perspectives

Abstract: This study investigates the perceptions of Gulf Cooperation Council (GCC) students and professional journalists regarding the quality of curriculum and training sessions that they received at the University and afterwards by looking at curriculum, training sessions and practical programmes related to journalism education, as well as the quality of academic staff and trainings for both GCC journalism students and professionals. A survey was administered to a random sample of 369 students at GCC universities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The following studies are related to the topic of our research concept of the study, which aimed to determine the quality of our education in relation to the challenges of professional activity on the basis of a survey of students majoring in journalism and practicing journalists (Ziani, Elareshi & Al-Jaber, 2018), establishment of three directions of development of specialized education of journalists (orientation, values and standards of journalism; social, cultural, political, economic, legal, ethical aspects; knowledge and intellectual component) (Martsikhiv, 2020), establishment of features of realization of the continuous training principles and definition of the specialists' need for additional competencies (Broiakovskyi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The following studies are related to the topic of our research concept of the study, which aimed to determine the quality of our education in relation to the challenges of professional activity on the basis of a survey of students majoring in journalism and practicing journalists (Ziani, Elareshi & Al-Jaber, 2018), establishment of three directions of development of specialized education of journalists (orientation, values and standards of journalism; social, cultural, political, economic, legal, ethical aspects; knowledge and intellectual component) (Martsikhiv, 2020), establishment of features of realization of the continuous training principles and definition of the specialists' need for additional competencies (Broiakovskyi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to our study, the emphasis is on the reasonability of conducting a survey of subjects of the educational process to establish motives for lifelong learning (Gogh & Kovari, 2018), to establish compliance with the content of specialized education of journalists with the main challenges of professional activity (Ziani, Elareshi & Al-Jaber, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, here again, science journalism appeared to be legging behind. According to Ziani et al (2018), Arab journalists used their practices and learned skills after completing their higher or secondary school education. has observed that journalists need basic science, technology, and medical knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In early 2006, 70 communication programs were available at various government and private Arab universities. According to Ziani et al (2018), there have been approximately 135 university programs teaching media and journalism over the last two decades.…”
Section: Journalism Education In the Arab Worldmentioning
confidence: 99%